(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this study were to describe the cultivation of marigolds. There were a total of 19 key informants who were studied using a qualitative approach. The results showed that 1) for cultivating marigolds, large varieties that yield fast-growing, early-flowering, and fruitful flowers should be selected. Marigold seeds have to be cultivated until the plants have 5–6 pairs of true leaves. Then, the plot has to be prepared by plowing, drying the soil, and increasing the quality of the plot by using fertilizers. Fertilizers are to be added at the bottom of the planting hole. Planting holes have to be dug and sprinkled with lime for 1–2 days. The marigold seedlings can then be transferred to the holes in the evening to reduce water loss. The plants have to be watered 1–2 times in the morning and the evening, and a small amount of manure and chemical fertilizers need to be added. The flowers and side buds have to be cut to increase the formation of new stems. Young large flowers can be collected at full bloom by cutting below the stem, as close to the base of the branch as possible.